Learning Management System Berbasis Web (Studi Kasus: STIKOM Poltek Cirebon) - Handayani, Cucu; Prasetyo, Diki (Jurnal ICT : Information Communication & Technology, 2020)
Currently, several universities are using the learning management system (LMS) application for administration, documentation, activity reporting, learning activity implementation, and online assignments. SIAKAD is a learning management system application that has been implemented at STIKOM Poltek Cirebon. At SIAKAD, students and lecturers can download and upload materials, view course data and schedule data. However, in SIAKAD there are several features that are still not fulfilled, such as checking attendance data and recapitulation, task recapitulation and automation of calculating final course grades. In this study the Lemskom Poltek Cirebon application was designed using the Asynchronous Learning method. Which aims to complement features that do not exist in SIAKAD. In the Lemskom Poltek Cirebon application, which is designed using the Asynchronous method, it is very appropriate because this method is not based on time and place and is very good at helping in the learning process. So that students can see for themselves the course schedule, their attendance data, and the assignments given by the lecturer at anytime and anywhere along with the information and values they get. Lecturers can see the recapitulation of attendance, and recapitulation of assignments as well as details of what grades are in the courses they teach in more detail and can calculate the final grade automatically.